Rural Aspirations: Reflections for Development Planning, Design and Localized Effects - Kai Mausch; Dave Harris; Javier Revilla Diez (The European Journal of Development Research, 2021)
In this editorial introduction to the Special Issue "Rural aspirations—Livelihood decisions and rural development trajectories", we outline current views on aspirations and their relevance for development research, projects and approaches. Using several examples from Africa,~we outline how the combination of the different theoretical perspectives, case studies and regional backgrounds provides deeper insights about the role of aspirations in shaping rural areas. The distinct entry points of the 'bottom up' local aspirations for future lives, the 'top down' aspirations as visions for change, and the process of negotiating between these provide novel insights into directions for development action as well as for future research in the field of aspirations in the development arena.
Keywords: 330; Rural development; Livelihood strategies; Choices; Participation; Development projects